Partnership work between Public Health and Health Psychology: introduction to a novel training programme - Robinson Clare; Marks Douglas; Dale Hannah; Dombrowski Stephan U; Gilinsky Alyssa S; Eades Claire; Ouzounidou Despina (BMC, 2010)
Abstract Background Public health services implement individual, community and population level interventions to change health behaviours, improve healthy life expectancy and reduce health inequalities. Understanding and changing health behaviour is complex. Integrating behaviour change theory and evidence into interventions has the potential to improve services. Methods Health Psychologists apply evidence and theories aimed at understanding and changing health behaviour. A Scottish programme is piloting the training of Health Psychologists within NHS contexts to address prominent public health challenges. Results This article outlines the details of this novel programme. Two projects are examined to illustrate the potential of partnership working between public health and health psychology. Conclusion In order to develop and improve behaviour change interventions and services, public health planners may want to consider developing and using the knowledge and skills of Health Psychologists. Supporting such training within public health contexts is a promising avenue to build critical NHS internal mass to tackle the major public health challenges ahead.